Lead poisoning after gunshot wound - Madureira, Paulo Roberto de; Capitani, Eduardo Mello De; Vieira, Ronan José (São Paulo Medical Journal, 2000)
CONTEXT: Despite the absence of symptoms in the majority of patients carrying lead bullet fragments in their bodies, there needs to be an awareness of the possible signs and symptoms of lead intoxication when bullets are lodged in large joints like knees, hips and shoulders. Such patients merit closer follow-up, and even surgical procedure for removing the fragments. OBJECTIVE: To describe a patient who developed clinical lead intoxication several years after a gunshot wound. DESIGN: Case report. CASE REPORT: A single white 23-year-old male, regular job as a bricklayer, with a history of chronic alcohol abuse, showed up at the emergency department complaining of abdominal pain with colic, weakness, vomiting and diarrhea with black feces. All the symptoms had a duration of two to three weeks, and had been recurrent for the last two years, with calming during interval periods of two to three weeks. Abdominal radiograms showed a bullet lodged in the left hip, with a neat bursogram of the whole synovial capsule. A course of chelating treatment using calcium versenate (EDTACaNa2) intravenously was started. After the chelation therapy the patient had recurrence of his symptoms and a radical solution for the chronic mobilization of lead was considered. A hip arthroplasty procedure was performed, leading to complete substitution of the left hip.